Exceptionally large, atypically located spindle cell lipoma. Issue 10 (31st October 2019) - John, Mitchell; Patel, Shaan; Joseph, George
Abstract : Spindle cell lipomas are a rare subtype of lipoma typically occurring in the shawl region of middle-aged men with a characteristic histological appearance consisting of mature adipocytes, ropey collagen and spindle cells. Those of extraordinary size or atypical anatomic location require a proper immunohistological workup to rule out more ominous malignancy. The authors report the rare presentation of a 54-year-old man with a large mass of the left palm causing discomfort and paresthesia for 6 months. Radiographs showed a radiolucent mass without mineralisation or bony involvement. MRI demonstrated a non-contrast-enhancing homogeneous lipomatous mass encompassing flexor tendons of the palm. Elective excisional biopsy and immunohistological analysis were consistent with spindle cell lipoma measuring 11 cm × 7 cm × 4 cm. This case is the largest spindle cell lipoma of the hand reported in the literature and appears to be the largest described in the upper extremity.